Friedel–Crafts approach to the one-pot synthesis of methoxy-substituted thioxanthylium salts - Tanaka, Kenta; Tanaka, Yuta; Kishimoto, Mami; Hoshino, Yujiro; Honda, Kiyoshi (Beilstein Journal of Organic Chemistry, 2019)
An efficient synthesis of methoxy-substituted thioxanthylium salts has been developed. The reaction of diaryl sulfides with benzoyl chlorides in the presence of TfOH smoothly proceeded to give the desired thioxanthylium salts in good yields. In their UV–vis spectra, the maximum absorption wavelengths of methoxy-functionalized thioxanthylium salts were observed at around 460 nm, which show a drastic red shift compared to the parent thioxanthylium salts. The present reaction provides a versatile access to functionalized thioxanthylium salts, and therefore it constitutes a promising tool for the synthesis of biologically and photochemically active molecules.
Keywords: Friedel–Crafts reaction; metal-free conditions; one-pot synthesis; photoredox catalyst; thioxanthylium salt

(untitled) - Wu, D.; Pisula, W.; Haberecht, M. C.; Feng, X.; Müllen, K. (Org. Lett., 2009)

(untitled) - Gannon, M. K., II; Holt, J. J.; Bennett, S. M.; Wetzel, B. R.; Loo, T. W.; Bartlett, M. C.; Clarke, D. M.; Sawada, G. A.; Higgins, J. W.; Tombline, G.; Raub, T. J.; Detty, M. R. (J. Med. Chem., 2009)

(untitled) - McKnight, R. E.; Onogul, B.; Polasani, S. R.; Gannon, M. K., II; Detty, M. R. (Bioorg. Med. Chem., 2008)

(untitled) - Gibson, S. L.; Holt, J. J.; Ye, M.; Donnelly, D. J.; Ohulchanskyy, T. Y.; You, Y.; Detty, M. R. (Bioorg. Med. Chem., 2005)

(untitled) - Freund, T.; Müllen, K.; Scherf, U. (Macromolecules, 1995)

(untitled) - Nishida, J.-i.; Miyagawa, T.; Yamashita, Y. (Org. Lett., 2004)

(untitled) - Suzuki, T.; Nishida, J.-i.; Ohkita, M.; Tsuji, T. (Angew. Chem., Int. Ed., 2000)

(untitled) - Okada, K.; Imakura, T.; Oda, M.; Kajiwara, A.; Kamachi, M.; Yamaguchi, M. (J. Am. Chem. Soc., 1997)

(untitled) - Hagel, M.; Liu, J.; Muth, O.; Estevez Rivera, H. J.; Schwake, E.; Sripanom, L.; Henkel, G.; Dyker, G. (Eur. J. Org. Chem., 2007)

(untitled) - Erabi, T.; Asahara, M.; Miyamoto, M.; Goto, K.; Wada, M. (Bull. Chem. Soc. Jpn., 2002)

(untitled) - Nealey, R. H.; Driscoll, J. S. (J. Heterocycl. Chem., 1966)

(untitled) - Ashby, J.; Ayad, M.; Meth-Cohn, O. (J. Chem. Soc., Perkin Trans. 1, 1973)

(untitled) - Krollpfeiffer, F.; Wißner, A. (Justus Liebigs Ann. Chem., 1951)

(untitled) - Rudorf, W.-D. (Sci. Synth., 2003)

(untitled) - Tanaka, K.; Kishimoto, M.; Ohtsuka, N.; Iwama, Y.; Wada, H.; Hoshino, Y.; Honda, K. (Synlett, 2019)

(untitled) - Tanaka, K.; Hoshino, Y.; Honda, K. (J. Synth. Org. Chem., Jpn., 2018)

(untitled) - Tanaka, K.; Sukekawa, M.; Hoshino, Y.; Honda, K. (Chem. Lett., 2018)

(untitled) - Tanaka, K.; Sukekawa, M.; Kishimoto, M.; Hoshino, Y.; Honda, K. (Heterocycles, 2019)

(untitled) - Tanaka, K.; Kishimoto, M.; Hoshino, Y.; Honda, K. (Tetrahedron Lett., 2018)

(untitled) - Tanaka, K.; Sukekawa, M.; Shigematsu, Y.; Hoshino, Y.; Honda, K. (Tetrahedron, 2017)

(untitled) - Tanaka, K.; Hoshino, Y.; Honda, K. (Heterocycles, 2017)

(untitled) - Tanaka, K.; Hoshino, Y.; Honda, K. (Tetrahedron Lett., 2016)

(untitled) - Tanaka, K.; Shigematsu, Y.; Sukekawa, M.; Hoshino, Y.; Honda, K. (Tetrahedron Lett., 2016)

(untitled) - Tanaka, K.; Kishimoto, M.; Sukekawa, M.; Hoshino, Y.; Honda, K. (Tetrahedron Lett., 2018)

(untitled) - Tanaka, K.; Omata, D.; Asada, Y.; Hoshino, Y.; Honda, K. (J. Org. Chem., 2019)